LANGUAGE ACQUISITION THEORIES: GENERATIVE OR USAGE-BASED APPROACH (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
Language is ability universal to man. This unique form of communication has been a characteristic of our species for some 200.000 years, yet the method of its acquisition is still a mystery to science. The aim of this paper is to present two opposing schools of developmental psycholinguistics: Noam Chomsky’s generative approach and Michael Tomasello’s usage-based approach, their principal ideas and claims, and to analyse the similarities and differences between the two. Special attention will be devoted to the criticisms aimed at both of these theories, as well as the new schools of thought emerging as a result of such critical reviews.
Keywords: generative approach, Universal Grammar, UB approach, modularity